Industry Payment to Vascular Neurologists: A 6-Year Analysis of the Open Payments Program From 2013 Through 2018. Issue 4 (April 2020) - Nalleballe, Krishna; Sheng, Sen; Li, Chenghui; Mahashabde, Ruchira; Annapureddy, Amarnath R.; Mudassar, Kamran; Pothineni, Krishna; Veerapaneni, Poornachand; Harada, Yohei; Chilkulwar, Abhishek; Ranabothu, Saritha; Brown, Aliza; et al.
Abstract : Background and Purpose—: Industry payments to physicians raise concerns regarding conflicts of interest that could impact patient care. We explored nonresearch and nonownership payments from industry to vascular neurologists to identify trends in compensation. Methods—: Using Centers for Medicare and Medicaid Services and American Board of Psychiatry and Neurology data, we explored financial relationships between industry and US vascular neurologists from 2013 to 2018. We analyzed payment characteristics, including payment categories, payment distribution among physicians, regional trends, and biomedical manufacturers. Furthermore, we analyzed the top 1% (by compensation) of vascular neurologists with detailed payment categories, their position, and their contribution to stroke guidelines. Results—: The number of board certified vascular neurologist increased from 1169 in 2013 to 1746 in 2018. The total payments to vascular neurologist increased from 99 749 in 2013 to 1 032 302 in 2018. During the study period, 16% to 17% of vascular neurologists received industry payments. Total payments from industry and mean physician payments increased yearly over this period, with consulting fee (31.1%) and compensation for services other than consulting (30.7%) being the highest paid categories. The top 10 manufacturers made the majority of the payments, and the top 10 products changed from drug or biological products to devices. Physicians from south region of the United States received the highest total payment (38.72%), which steadily increased. Payments to top 1% vascular neurologists increased from 64% to 79% over the period as payments became less evenly distributed. Among the top 1%, 42% specialized in neuro intervention, 11% contributed to American Heart Association/American Stroke Association guidelines, and around 75% were key leaders in the field. Conclusions—: A small proportion of US vascular neurologists consistently received the majority of industry payments, the value of which grew over the study period. Only 11% of the top 1% receiving industry payments have authored American Heart Association/American Stroke Association guidelines, but ≈75% seem to be key leaders in the field. Whether this influences clinical practice and behavior requires further investigation. Abstract : Supplemental Digital Content is available in the text.